Trabalho com famílias na assistência social: novas expressões do conservadorismo? - Eufrásio, Amanda (2014)
nowadays is what this research is focused on.It was based on the assumption that conservative practices (re) update under Social Service, that we aimed in this research in order to grasp ways of being conservative when executing the profession, more specifically, in the area of social assistanceFor this, besides the literature survey on the topic, the research went on based on qualitative methodology by conducting semi structured interviews with five social workers (randomly selected) who work in Reference Centers for Social Welfare (CRAS), in four cities on the Alto Tiete area, in Sao Paulo, being: Santa Isabel, Aruja, Mogi das Cruzes e Guararema. These people were picked according to the population dynamics of their cities and the consolidation degree of the work with families under social assistancein the first chapter; we go on social-historical meanings of the conservatism and its impact on the profession of Social Work.In the second chapter, we situate the context in which they develop social policies nowadays and we cover the main features of social assistance policy in Brazil today.In the third chapter, we analyze the data collected.As a part of the research results, we figured that: 1. 1 There are positive changes in ways of understanding who are the families that seek for social assistance, but stigmas and prejudices on these people are still shown in professional execution; 2 - the way professionals look upon the people that make use of the social assistance and the possibilities of facing social is influenced by conservative tendencies as the politicization of the meaning of poverty; 3 families are disciplined to keep a satisfactory performance during their participation on the income transfers programs; 4 The social work with families through the Protection Service and Integral Care of Family (PAIF) is presented as an attempt to break in with conservative practices in this sphere of professional activity and some (as) professionals take ownership of these service proposals to face the effects of the conservatism of the professional; 5 families are educated to achieve autonomy, which revealed the positive aspects in the sense of deconstruct welfare practices and to give poor families access to their rights and the policies and public services, as well as claiming their improvement.However, the survey also showed a tendency to individualize problems that are social responsibility and, increasingly, families for their poverty condition